A Three-Wave Longitudinal Study of Moderated Mediation Between High-Performance Work Systems and Employee Job Satisfaction: The Role of Relational Coordination and Peer Justice Climate - Haider, Sajid; De-Pablos-Heredero, Carmen; De-Pablos-Heredero, Monica (Frontiers in Psychology, 2020)
Existing literature lacks studies that examine the indirect effect of high-performance work systems (HPWSs) on employee job satisfaction through employee–employee relations. Moreover, less is known about the boundary conditions of this indirect effect. This study sought to longitudinally examine the mediating role of a specific form of employee–employee relations—relational coordination—in the relationship between HPWS and job satisfaction. Data were collected in three waves from the employees of commercial banks (N = 322). Partial least squares structural equation modeling was used for data analysis. Results from multiple linear autoregressive longitudinal analysis indicate that HPWSs predict relational coordination, which in turn partially mediates the HPWS–job satisfaction relationship. Perceptions of peer justice climate provide boundary conditions for the aforementioned mediating effect. This study contributes to existing literature by explaining moderated-mediation mechanisms through which HPWSs predict employee job satisfaction. Managers can strengthen the effect of HPWS on employee–employee relations and subsequent effect on employee job satisfaction by promoting peer justice climate in organizations.